Interactive and non-interactive hybrid immigrants schemes for ant algorithms in dynamic environments - Mavrovouniotis, Michalis; Yang, Shengxiang (My University, 2014)
Dynamic optimization problems (DOPs) have been a major challenge for ant colony optimization (ACO) algorithms. The integration of ACO algorithms with immigrants schemes showed promising results on different DOPs. Each type of immigrants scheme aims to address a DOP with specific characteristics. For example, random and elitism-based immigrants perform well on severely and slightly changing environments, respectively. In this paper, two hybrid immigrants, i.e., non-interactive and interactive, schemes are proposed to combine the merits of the aforementioned immigrants schemes. The experiments on a series of dynamic travelling salesman problems showed that the hybridization of immigrants further improves the performance of ACO algorithms.
Keywords: Traveling salesman problem; ACO algorithms; Ant algorithms; Ant Colony Optimization algorithms; Changing environment; Dynamic environments; Dynamic optimization problem (DOP); Travelling salesman problem; Ant colony optimization